(untitled) (Journal of Philosophy Culture and Political Science, 2018)
To reveal the religious views of the outstanding Kazakh thinker Akyt kazhi Ulimzhyuly, it is necessary first of all to characterize the religious education he received, his writings, raised problems on religious topics in the context of the traditions of historical time and that era. The definition of religious philosophical beliefs from the religious position, sung by the poet in poems based on Koran Karime and hadithssharifs, is the main task of this article. The purpose of the article is to analyze the correspondence of the religious outlook of Akyt to the faith of the madhhab of Maturidi. The article gives a comparative analysis of the conformity of the religious views of the teacher Akyty who built the madrassahs on both sides of the Altai and trained the children, the traditional religious system of the Kazakh people, their spiritual accord with the views of Maturidi. Key words: Akyt, religion, madhab, Kalam, fiqh, akida, personality, school, comparison.